2020
DOI: 10.4081/monaldi.2020.1214
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous lung abscess drainage: revisiting the old gold standard

Abstract: Lung abscess is defined as the necrosis of lung tissue with cavity formation due to varied etiology. The treatment of lung abscesses is medical involving antibiotics and chest physiotherapy. The failure of medical line of management requires an invasive surgical or percutaneous approach for drainage and control of infection. While the literature is ample regarding the surgical approach, it is rather scarce on the percutaneous approach. The percutaneous drainage has been most studied with computed tomography gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, with the advent of potent antibiotics, lung abscesses respond to medical therapy in 80%-90% of cases. A review of the literature showed acceptable outcomes for percutaneous drainage of lung abscesses not responding to medical treatment, with some studies reporting up to 80%-100% success rate [ 4 - 6 ]. This is especially useful in patients who have a significant morbidity and mortality risk for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the advent of potent antibiotics, lung abscesses respond to medical therapy in 80%-90% of cases. A review of the literature showed acceptable outcomes for percutaneous drainage of lung abscesses not responding to medical treatment, with some studies reporting up to 80%-100% success rate [ 4 - 6 ]. This is especially useful in patients who have a significant morbidity and mortality risk for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In lung abscesses measuring 6-8 cm, not responding to initial antibiotic therapy, percutaneous drainage is recommended. The complication rate for percutaneous abscess drainage has been reported to be around 8% to 16%, with a mortality rate of around 4% [ 4 - 6 ]. Complications include catheter blockage necessitating repeat procedures, pneumothorax, hemothorax, hemoptysis and need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matarese et al ( 4 ) used 14 G needle to aspirate lung abscesses under ultrasound guidance in a series of eight patients. They used a 14 G needle because no pigtail catheters were available at the hospital.…”
Section: Pttdmentioning
confidence: 99%
“…Moreover, any abscess greater than 6 cm in diameter is less likely to respond to antibiotics and frequently requires additional drainage procedures ( 2 , 3 ). There is a higher likelihood of treatment failure when treated with antibiotics alone in immunocompromised patients, abscess with underlying malignancy, advanced age, decreased level of consciousness, or infection with certain organisms, such as Klebsiella pneumoniae , Pseudomonas aeruginosa , and Staphylococcus aureus ( 4 ). Despite systemic antibiotic treatment, persistent clinical symptoms, or presence of radiologic evidence of active abscess, warrant a more definitive therapy with invasive procedures and, ultimately surgery.…”
Section: Introductionmentioning
confidence: 99%